Blood Pressure and Cholesterol Screening as a Preventive Measure for Degenerative Diseases in the Elderly - Diatri, Devita; Joharlina, Lourensya Berta; Kurniawan, Dwi Agus; Rakhmawatie, Maya Dian; Zulizar, Alif Adlan (Universitas Negeri Semarang, 2025)
The elderly are one of the highest risk groups for developing degenerative diseases such as hypertension and dyslipidemia. This community service is held to promote the early detection of older adults at risk of degenerative diseases and improve knowledge of healthy lifestyles. The activity was held on June 18, 2025, in Wreda Harapan Ibu Semarang Nursing Home, Semarang, Indonesia. A total of 19 older women aged 60 to 90 years were screened for their blood pressure and total cholesterol levels. Study participants were diagnosed with hypertension in 84.2% and with high cholesterol in 63.2% of cases as a result of the examination. Post-examination, participants were provided health education emphasizing the need to control blood pressure and cholesterol through the consumption of healthy diets, light physical activities, and drug adherence. This study has shown the efficacy of combining health checks and education as a promotive and preventive strategy for degenerative diseases in the institutionalized elderly. Early discovery is beneficial for early prevention, and health education plays an important role in helping the elderly remain conscious and independent, thereby maintaining good health. This trend is in line with the paradigm of prevention-oriented healthcare services, promoting and protecting health rather than waiting for illness. The findings from the activity also underscore the need for continuation and sustainability of such programs, given the high prevalence of hypertension and dyslipidemia. Arguably, the disease burden is likely to be greater if not managed in an organized manner.